(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
In the article the poetry of vagants considered as a product of the subculture of wandering students of the Mature Middle Ages. Considerable attention is paid to understanding of the worldview, life attitudes, ethical and aesthetic ideals of this social class and the peculiarities of their expression in works. It is pointed out on the peripatetic lifestyle of vagants; it is noted that their poetry was mostly anonymous; it is indicatedthe dominants in the creativity of Primas of Orleans, Archpoetof Cologne, Walter Chatilion.